An Assessment of Beneficiaries’ Satisfaction of the Management of Loan Contract Components by Farmer Cooperative Societies in Edo State, Nigeria - Grace Oghenerobor Alufohai; Tosan Jolomi Okorosobo (International Journal of Agricultural Management and Development, 2013)
The study assessed beneficiaries’ satisfaction in the managementof loag-contract components by cooperatives involved inthe farm credit delivery in Edo State. The objective was toidentify the components of the farm loan contract, examine themanagement strategies and rate the beneficiaries’ satisfaction ofsuch management strategies. This was done by purposivelyselecting 40 cooperatives involved in farm credit delivery inOredo, Egor and Ikpoba-Okha LGAs of Edo State where thereis a proliferation of cooperatives who are actively involved infarm credit delivery. Data were analyzed using descriptivestatistics, queuing model and satisfaction indices.Results showedthe main loan-contract components to be loan volume, repaymentregime, interest rates charged, default management, collateralrequired, timeliness and loan monitoring. Average beneficiaries’index was 4.28 out of 5 indicating high satisfaction originatingfrom good queue management with traffic density of 1.12,moderate interest rate of 9% p.a, active loan monitoring, nophysical collateral, timely disbursement of loan and accommodativerepayment regime. Only individual loan volumes were low as aresult of inadequate loanable fund. Study recommends that cooperativesocieties should take advantage of external sources offunds to boost the volume of their loanable funds.